2020
DOI: 10.1155/2020/5262351
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity-Stratified Analysis of the Association between TNF-α Genetic Polymorphisms and Acute Kidney Injury: A Systematic Review and Meta-Analysis

Abstract: Background. Several studies have reported conflicting findings regarding the association between tumor necrosis factor-alpha (TNF-α) genetic polymorphisms and acute kidney injury (AKI). Therefore, we performed this meta-analysis to further investigate whether TNF-α variants are related to AKI susceptibility. Methods. A comprehensive search of observational studies on the association of TNF-α polymorphism with AKI susceptibility was conducted in the PubMed, Cochrane, and Embase databases through February 10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A recently published study has declared that one tumor necrosis factor-α (TNF-α) single nucleotide polymorphisms (SNPs)—rs1800629 polymorphism exhibited a trend toward AKI susceptibility with ethnic differences. 51 Continued studies are recommended to focus on ECMO across different ethnicities. The timing of onset of AKI by any definition is indeed difficult to establish, which is why some studies consider that the three traditional definitions are limited and insufficiently accurate to effectively define ECMO-related AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study has declared that one tumor necrosis factor-α (TNF-α) single nucleotide polymorphisms (SNPs)—rs1800629 polymorphism exhibited a trend toward AKI susceptibility with ethnic differences. 51 Continued studies are recommended to focus on ECMO across different ethnicities. The timing of onset of AKI by any definition is indeed difficult to establish, which is why some studies consider that the three traditional definitions are limited and insufficiently accurate to effectively define ECMO-related AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Early use of risk stratification algorithms and potentially, machine-learning models [115,116], factoring in new AKI biomarkers, may help improve perioperative outcomes. More AKI studies are needed addressing pediatric patients and genetic risk factors [117] and clarifying the utility of GDFT.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with most previous studies. A systematic review and meta-analysis showed that rs1800629 GA and AA genotypes had a higher trend of AKI in Asians [14]. The homozygous AA genotype was found to have a relationship with CRF and ESRD [15], and A allele had a higher risk of acute rejection in first kidney transplant subjects [36].…”
Section: Discussionmentioning
confidence: 99%
“…The renal actions of TNF-α include the regulation of hemodynamic and excretory function in the kidney, by inducing renal vasoconstriction and hypofiltration [12,13]. Some studies have demonstrated that TNF-α gene polymorphisms are associated with acute kidney injury (AKI), chronic renal failure (CRF), and ESRD [14,15]. Nevertheless, the relationship between metal-related renal function change and TNF-α gene polymorphisms has not been published.…”
Section: Introductionmentioning
confidence: 99%